Evaluation of the efficiency of three oil extraction equipments with different oil palm genotypes (Elaeis sp.) - Navarrete Párraga, Mercedes Elizabeth; Zambrano Marcillo, Silvia Madeleim; Zambrano Sabando, Walter Ramón; Romero Pizarro, Martha Alicia; Racines Jaramillo, Marcelo Rafael; Paredes Puga, Ernesto Ricardo; Quintero Roman, Leonardo Andres; Ortega Cedillo, Digner Santiago (Enfoque UTE, 2020)
This work was performed in the oil extraction laboratory of the African Palm Program, of the Experimental Station “Santo Domingo” of the INIAP. The main objective was to determine the efficiency of three oil extraction equipments, in three oil palm genotypes. The equipments used were Velp solvent extractor, Soxhlet extractor and a 1500 psi hydraulic press. The genotypes evaluated are part of the germplasm bank of the Palm Program at INIAP: Elaeis guineensis (african palm), Elaeis oleifera (american palm) and E. oleifera x E. guineensis (interspecific hybrid). The experimental design was a complete random design (DCA), with 20 observations, followed by student’s test and Tukey test at a 5 significance, to determine differences between treatment means. The results showed highly significant differences between the different factors evaluated. The higher percentage of oil per bunch was obtained with the genotype E. guineensis in the Soxhlet extractor (18.43 %) and the lowest percentage for E. oleifera with the hydraulic press (0.34 %). The analysis of costs determined that the lowest cost was obtained with the hydraulic press with USD 8,20 per sample.